Effect of Finger Millet and Sorghum Replacing Corn in Presence of Soy Oil / Fish Oil and Enzymes on Performance of Broilers - Reddy, K. Venkata; Malathi, V.; Reddy, B.S. Venkatarami; Kumar, K.S. Pratap; Umakantha, B.; Jayanaik (International Journal of Poultry Science, 2008)
A trial was conducted in commercial day old broiler chicks to study the effect of replacing corn with finger millet and sorghum and supplementation of soy oil / fish oil and Non-starch polysaccharide degrading enzymes to these diets. Basal diet was formulated using corn, soy bean meal and pea nut extraction. In the test diets, 50% of the corn was replaced with either finger millet or sorghum or equal parts of the both and then supplemented with soy oil / fish oil and enzyme mixture. Weekly body weight, feed intake, feed conversion ratio, livability were recorded. Body weight slightly improved in the test diets than the control. Compared to the soy oil, fish oil was better in improving body weight, feed efficiency and livability. Though supplementation of enzymes did not significantly improve body weight and feed efficiency, slight numerical improvement was noticed in fish oil supplemented groups.